2001
DOI: 10.1042/bj3570465
|View full text |Cite
|
Sign up to set email alerts
|

FK506-binding protein of the hyperthermophilic archaeum, Thermococcus sp. KS-1, a cold-shock-inducible peptidyl-prolyl cis–trans isomerase with activities to trap and refold denatured proteins

Abstract: 465 FK506-binding protein of the hyperthermophilic archaeum, Thermococcus sp. KS-1, a cold-shock-inducible peptidyl-prolyl cis-trans isomerase with activities to trap and refold denatured proteins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The solubility of p53 was drastically improved by TcFKBP18 (lanes 4 and 5, Fig. 5B), agreeing well with the reported ability of this molecular chaperone to trap and refold many heterologous misfolded recombinant proteins (13,35). Further testing of the power and versatility of TcFKBP18 was done in the next application, PIMAX-CoP.…”
Section: Fig 3 Phosphorylation Enhances Tau Fibrillization In Vitrosupporting
confidence: 64%
See 3 more Smart Citations
“…The solubility of p53 was drastically improved by TcFKBP18 (lanes 4 and 5, Fig. 5B), agreeing well with the reported ability of this molecular chaperone to trap and refold many heterologous misfolded recombinant proteins (13,35). Further testing of the power and versatility of TcFKBP18 was done in the next application, PIMAX-CoP.…”
Section: Fig 3 Phosphorylation Enhances Tau Fibrillization In Vitrosupporting
confidence: 64%
“…Specifically, we chose TcFKBP18, an FK506-binding protein from the hyperthermophilic archaeon Thermococcus sp. KS-1 (35). Unlike other multicomponent E. coli proteinfolding machinery such as DnaJ/DnaK and GroEL/GroES, TcFKBP18 acts alone to trap and refold denatured proteins in vitro and can increase the solubility of several recombinant proteins in vivo (13) when fused physically to these clients.…”
Section: Fig 3 Phosphorylation Enhances Tau Fibrillization In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Archaeal FKBPs have been classified into two groups: 16-to 18-kDa FKBPs (short-type FKBPs) and 26-to 33-kDa FKBPs (long-type FKBPs) (20). It has been reported that the short-type FKBP from archaea possesses not only PPIase activity but also chaperone-like protein folding activity in vitro (4,13). The long-type FKBPs consist of an N-terminal FKBP domain, which is homologous to that in the short-type FKBPs, and an adjacent C-terminal domain comprising ca.…”
Section: Fk506 Binding Protein (Fkbp) Is a Family Of Peptidyl-prolylmentioning
confidence: 99%